An Analysis of Islamic Family Law on Divorce Due to Migration (Merantau) Among the Mandar Community in Polewali Mandar Regency - Riswan, Riswan; Hasnawati, Hasnawati; Latif, Abdul; Solimin, Solimin (LPPPIPublishing, 2025)
This study is motivated by the increasing divorce rate in Indonesia, including in Polewali Mandar Regency, where migration (merantau) has become one of the dominant contributing factors. The merantau tradition, which has long been an integral part of the Mandar community’s social identity, often disrupts family life due to physical distance, limited communication, and economic pressures. This research aims to analyze the influence of migration on family resilience and to examine its implications from the perspective of Islamic Family Law. The study employs a qualitative approach with a socio-legal research design, utilizing interviews, observations, and document analysis interpreted through a descriptive-analytical framework. The findings reveal that migration contributes to the rise of divorce cases within the Mandar community as a result of shifting family roles, physical absence, and weakened emotional communication. Nevertheless, traditional mediation mechanisms and Islamic values continue to play a significant role in resolving domestic conflicts. The implications of this study highlight the necessity of integrating Islamic legal principles with local wisdom to strengthen family resilience among migrant communities. The originality of this research lies in its interdisciplinary analysis that bridges Islamic law and Mandar culture in explaining divorce caused by migration as a complex socio-religious phenomenon.